BIOPROSPECTING OF BACTERIAL SYMBIONT OF Tunicate Didemnum molle FROM SAMBANGAN, KARIMUNJAWA ISLANDS - Miftahuddin Majid Khoeri; Ocky Karna Radjasa; Agus Sabdono; Herawati Sudoyo (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Coral reef is a productive ecosystem with high biodiversity in the sea and being targeted to find a useful bioactive compound. However, the serious problem in development of bioactive compounds from marine invertebrate is the supply problem, because to get a small amounts of active compounds a massive numbers of sea organisms are needed. Tunicate is an animal in coral reef ecosystem that produces many bioactive compounds with pharmacological activities, such as, antibacterial, antitumor, and anticancer compounds. It has been reported that bacterial symbionts of coral reef invertebrates may synthesize the same compounds as the host. The purposes of this research are to isolate and to identify microbes which have antibacterial activity against MDR bacteria based PCR 16S rRNA and to detect the existence of PKS and NRPS biosynthetic gene fragments from tunicate bacteria of Didemnum molle. Out of 15 bacterial isolates, one isolate showed antibacterial potential against Escherichia coli and Staphylococcus sp. Molecular identification result showed that TS2A5 bacterium has a homology of 99 % with Virgibacillus sp. strain GSP17 16S ribosomal RNA gene. This isolate was also capable of amplifying NRPS gene fragment.